AUDIT@eduroam: A Security Auditing Tool for the eduroam Infrastructure - Carvalho, Fabiano Losilla de; Oliveira, Luciana Pereira; Melo, Erick Lazaro (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
The eduroam federation enables global academic mobility through IEEE 802.1X and RADIUS standards. However, non-compliance with RFC 7593 leaves user credentials vulnerable. To address this, AUDIT@eduroam introduces a three-stage automated framework: (1) data acquisition, (2) static client-side analysis of CAT profiles, and (3) dynamic server-side verification via RADIUS logs. Validation across 148 IdPs over three execution cycles revealed that theoretical compliance (39.86%) drops to just 2.70% in dynamic tests, with 81.08%-83.11% of institutions failing due to expired certificates and identity exposure. These findings underscore a state of insecurity within the infrastructure, highlighting the need for continuous, automated monitoring of the network.